EFFICACY AND SAFETY OF NIFEDIPINE GASTROINTESTINAL THERAPEUTIC SYSTEM VERSUS RAMIPRIL IN CHINESE AND EUROPEAN PATIENTS WITH HYPERTENSION. (June 2022) - Zhang, Wei; Liu, Chang-Yuan; Bilo, Grzegorz; Soranna, Davide; Zambon, Antonella; Kyriakoulis, Konstantinos; Kollias, Anastasios; Ceravolo, Isabella; Cassago, Silvia; Pengo, Martino; Stergiou, George S.; Wang, Ji-Guang; et al.
Abstract : Objective: In a post-hoc analysis of a multinational, randomized trial, we investigated whether the efficacy and safety of ramipril and nifedipine gastrointestinal therapeutic system (GITS) differed between the Chinese and European patients with hypertension. Design and method: Previously treated and untreated (2 weeks washout) male and females patients aged 35–75 years with a clinic systolic/diastolic blood pressure (BP) over 140/90 mmHg and a daytime ambulatory systolic/diastolic BP over 135/85 mmHg were randomly assigned to ramipril 10 mg or nifedipine GITS 30 mg for 10 weeks in monotherapy (main study) and for an extension to 12 months with the possible up-titration of the monotherapy and combination with a diuretic or an alpha-blocker (extension study). BP lowering efficacy was evaluated for clinic, ambulatory and home BP at 10 weeks and 12 months follow-up. Results: The 67 Chinese and 101 European patients significantly (P < 0.01) differed in several major characteristics such as age (50.9 vs. 54.6 years), body-mass index (24.5 vs. 27.0 kg/m2), heart rate (75.0 vs. 70.8 beats/minute) and clinic (87.9 vs. 92.5 mmHg) and nighttime diastolic BP (79.3 vs. 75.9 mmHg), but did not differ in any characteristic between the ramipril and nifedipine GITS groups within each ethnicity (P> 0.05). BP was similarly reduced in the two treatment groups in both Chinese and European patients, except for a significantly greater daytime systolic/diastolic BP reduction in the ramipril than nifedipine-GITS group in the Chinese patients (+7.4/ + 4.1 mmHg, P = 0.02). The Chinese, compared with European patients, had a higher incidence rate of all adverse events (13 [38.2%] vs. 14 [28.6%], P = 0.48) and dry cough in the ramipril group (11 [32.4%] vs. 3 [6.1%], P = 0.003) but lower incidence rate of all adverse events in the nifedipine GITS group (4 [12.1%] vs. 18 [34.6%], P = 0.02). Conclusions: In the Chinese and European patients with hypertension, ramipril and nifedipine GITS had similar BP lowering efficacy, but different incidence rate of adverse events.